A brief history of the Italian marine biology. Issue 1 (1st January 2019) - Cattaneo-Vietti, R.; Russo, G. F.
Abstract: This paper is a short history of Italian marine biology, starting from the mid 16th century. During the Renaissance, a profound curiosity for marine sciences animated the scientific thought and several Italian naturalists started to collect rare and unusual marine items, sometimes acting with little critical sense towards medieval unbelievable legends. The 17th and 18th centuries saw a development of botany and zoology as modern disciplines and Italian scholars started to study the Mediterranean fauna and flora. They became active mainly at the Universities of Trieste, Venice, Palermo, Naples, Rome and Genoa and in other scientific institutions that arose under the different political regimes in which Italy was divided at that time. The Kingdom of Italy, born in 1861 with enormous financial difficulties, was interested in reaching an international scientific limelight: hence, some oceanographic expeditions were organized all around the world with a significant collection of data and specimens. The scientific interest for sea life increased and became at international level at the end of the 19th century, with the foundations of the first shore-based Zoological Stations in Trieste and Naples. At the beginning of the 20th century, intensive studies of inshore benthic communities by dredging and, afterwards by diving, started concurrently with those on structure and dynamics of plankton and fish populations which yielded a significant knowledge of the marine life from the Mediterranean continental platform. After the Second World War, the fundamental studies conducted at the Zoological Station of Naples on genetics, embryology and developmental biology using marine organisms as study models, were spread to different universities, going to constitute an Italian school of experimental embryology of international value. Today, the modern Italian marine biology is increasingly multi-disciplinary, requiring the participation of biochemists, geneticists and mathematicians and it opens up to new frontiers often linked to the global changes.